2008
DOI: 10.1111/j.1468-2257.2007.00403.x
|View full text |Cite
|
Sign up to set email alerts
|

Producer Service Linkages and Industrial Innovation: Results of a Twelve‐Year Tracking Study of New York State Manufacturers

Abstract: This paper documents the results of a twelve-year tracking study of New York State (NYS) manufacturers of scientific instruments (1994-2005). The main goal of the tracking exercise was to probe for firm-level changes in the use of external producer services, notably in technical fields such as industrial design, contract research, and engineering. Another goal was to assess the extent to which these outside inputs have been contributing to the product innovation efforts of users. The results show that innovati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 45 publications
(62 reference statements)
0
35
0
4
Order By: Relevance
“…Furthermore-and this has been a fundamental change over the last 20 years (Macpherson, 2008)-geographic isolation no longer implies isolation from the news cycle, from technical changes or from scientific discovery: quasi-ubiquitous access to the Internet means that, except for firms whose innovations rely on immediate exploitation of knowledge, the small time-lag that exists between its production and wide availability has negligible effects (Shearmur, 2015). A further key change brought about by the Internet is the capacity of firms in remote areas to effectively identify shortlists of potential information sources and collaborators, thereby targeting communications and contacts, and generating sizable efficiency gains when travelling for face-to-face encounters (Macpherson, 2008). A further key change brought about by the Internet is the capacity of firms in remote areas to effectively identify shortlists of potential information sources and collaborators, thereby targeting communications and contacts, and generating sizable efficiency gains when travelling for face-to-face encounters (Macpherson, 2008).…”
Section: Diverse Diversities: Diversity In Small Towns and Remote Smentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore-and this has been a fundamental change over the last 20 years (Macpherson, 2008)-geographic isolation no longer implies isolation from the news cycle, from technical changes or from scientific discovery: quasi-ubiquitous access to the Internet means that, except for firms whose innovations rely on immediate exploitation of knowledge, the small time-lag that exists between its production and wide availability has negligible effects (Shearmur, 2015). A further key change brought about by the Internet is the capacity of firms in remote areas to effectively identify shortlists of potential information sources and collaborators, thereby targeting communications and contacts, and generating sizable efficiency gains when travelling for face-to-face encounters (Macpherson, 2008). A further key change brought about by the Internet is the capacity of firms in remote areas to effectively identify shortlists of potential information sources and collaborators, thereby targeting communications and contacts, and generating sizable efficiency gains when travelling for face-to-face encounters (Macpherson, 2008).…”
Section: Diverse Diversities: Diversity In Small Towns and Remote Smentioning
confidence: 99%
“…This line of reasoning is consistent with Puga's (2010) questions concerning the nature of agglomeration economies: whereas static agglomeration externalities (linked to the division of labour, to shared infrastructure and to labour availability) have been well documented empirically, dynamic externalities-and in particular the connection between diversity of larger cities and firm-level learning-have not been observed so unequivocally (Fitjar & Rodríguez-Pose, 2017). Once collaboration or information exchanges are established (which often requires face-to-face-Bathelt, 2011), they can be maintained at a distance (Macpherson, 2008): indeed, external contacts are particularly important in small towns and rural settings because without outside information and knowledge there is danger of lock-in (Boschma, 2005), as smaller groups of people more quickly share their ideas and tend towards homogeneity (Fuijta, 2009). Once collaboration or information exchanges are established (which often requires face-to-face-Bathelt, 2011), they can be maintained at a distance (Macpherson, 2008): indeed, external contacts are particularly important in small towns and rural settings because without outside information and knowledge there is danger of lock-in (Boschma, 2005), as smaller groups of people more quickly share their ideas and tend towards homogeneity (Fuijta, 2009).…”
Section: Diverse Diversities: Diversity In Small Towns and Remote Smentioning
confidence: 99%
“…Using survey data on 50 manufacturing firms in the US, MacPherson and Vanchan (2010) find that the purchase of industrial design services is complementary to in-house core competences. The outsourcing of industrial design services is often related to the acquisition of superior services or totally new services, which is unlikely to reduce in-house services (see also MacPherson, 2008). Francois (1990) also finds that producer services and in-house service functions are complementary based on a theoretical model.…”
Section: Empirical Model and Theoretical Backgroundmentioning
confidence: 99%
“…Guerrieri (2005) found that KIBS has a significant effect on the technology-intensive manufacturing and little effect on labor-intensive ones [12]. Macpherson (2008) confirmed the above views by studying high knowledge and technology intensive services such as finance, communications, commerce, etc [13].…”
Section: Literature Reviewmentioning
confidence: 70%